Bridging Engagement and Comprehension: Evaluating Canva’s Effectiveness as a Digital Worksheet in Arabic Writing - Nurul Aini N. Pakaya; Muhammad Jundi; Suharia Sarif; Chaterina Puteri Doni; Nur Hasaniyah; Velit Seyit (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2025)
This study examined the effectiveness of using Canva as a digital worksheet to enhance students’ comprehension of the Insya’ (Arabic writing) subject in an Indonesian boarding school context, employing a mixed-methods approach with a sequential explanatory design. The analysis compared post-test results between control and experimental groups and was corroborated by data from questionnaires and classroom observations. The sample consisted of 72 male junior high school students, with 133 respondents completing the questionnaire. The findings indicated that the experimental group demonstrated higher levels of comprehension; however, only half of the students reported substantial improvement, despite 93.2% expressing positive responses toward the use of Canva. This discrepancy suggested that high learner acceptance did not necessarily correspond to improved comprehension, as no significant positive correlation was found between students’ acceptance and learning outcomes. Nevertheless, the use of Canva significantly enhanced student engagement, motivation, and collaboration, indicating its effectiveness when applied selectively for conceptual learning purposes.